DILEMA REFORMASI DEWAN KEAMANAN PERSERIKATAN BANGSA BANGSA: TINJAUAN TERHADAP TANTANGAN STRUKTURAL DAN KEGAGALAN DALAM PENYELESAIAN KONFLIK GLOBAL - Syarifah , Claudia (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2024)
This article discusses the legitimacy dilemma of the UN Security Council by examining structural challenges and failures in resolving global conflicts. The author criticizes the Council's structure, which is dominated by the P5 (United Kingdom, China, France, Russia, United States), stating that it impedes effective responses to contemporary challenges. Reform of the UN Security Council is deemed necessary, particularly regarding the veto power, expansion of membership, and regional representation. In the context of international agreements, the author addresses power differentiation, especially the veto power of the P5 and the role of multinational corporations. This writing illustrates the hierarchy and power dynamics within the UN Security Council, highlighting perspectives on legitimacy, national interests, and global exploitation.